Hydrophilic interaction chromatography a guide for practitioners - Olsen, Bernard A., 1953-; Pack, Brian W., 1970- (Chemical analysis ;, 2013)
"This book provides background information, guidance for method development, and a discussion of applications in the field of hydrophilic interaction chromatography (HILIC.) The book serves as a valuable reference tool for scientists confronted with an analysis problem involving polar compounds to determine if HILIC would be a good choice to pursue and helps them in choosing initial experimental conditions. The book gives a detailed description of the HILIC retention mechanisms and specific information regarding application areas spanning a wide range of industries.Topics include: HILIC retention mechanisms, Stationary Phases for HILIC, HILIC Method Development, Pharmaceutical and Other Applications of HILIC, HILIC for Drug Discovery, HILIC in Two-Dimensional Separations"--